A Review of the Technology Readiness Index (TRI) 2.0 in Learning Management System Contexts - Fiosandi Rizky Novalino; David Sukardi Kodrat (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
In the digital transformation era, Learning Management Systems (LMS) such as Moodle, Canvas, Blackboard, and Google Classroom have become the backbone of modern education, yet their success depends not only on infrastructure but also on users’ readiness to adopt technology. This study aims to systematically review and synthesize empirical research applying the Technology Readiness Index (TRI) 2.0 within LMS contexts to identify trends, key findings, and research gaps. Adopting the PRISMA-guided Systematic Literature Review (SLR) method, 1,234 records were screened across major academic databases, resulting in 35 eligible articles published between 2015 and 2024. Descriptive and thematic analyses reveal that the motivator dimensions Optimism and Innovativeness consistently promote LMS adoption, satisfaction, and engagement, while the inhibitor dimensions Discomfort and Insecurity hinder effective use. Most studies employ quantitative cross-sectional surveys in higher education, with limited research in K-12 or corporate settings. The findings underscore that TRI 2.0 serves as a robust framework for understanding psychological readiness in technology-mediated learning and highlight the need for longitudinal, qualitative, and cross- contextual studies. This review concludes that enhancing technology readiness is essential for maximizing LMS effectiveness, fostering sustainable user engagement, and guiding future pedagogical innovation in digital education.